IDENTIFIKASI MUTU NATA KULIT BUAH NAGA (Hylocereus undatus) DENGAN VARIASI KONSENTRASI SUKROSA - Hesti Nur'aini; Eva Ramalia Sari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2016)
As a byproduct of the dragon fruit (Hylocereus undatus) consumption, dragon fruit peel still contains nutritional components that potential to be a material of food processing. In nata processing, sugar was used as a carbon source for Acetobacter xylinum bacterial growth. The purpose of this study was to characterize the physical, chemical and organoleptic nata of dragon fruit peel. The experiment was done with two steps : processing of nata of dragon fruit peel with sucrose treatment (2 %, 4 %, 6 %, 8 % and 10 %), then the physical analysis (thick pellicle, pellicle weight and texture), the analysis of chemical properties (fiber content) and analysis of organoleptic to determine the level of hedonic scale for appearance, taste and texture, using 20 trained panelists. The analysis showed that the pellicle weight ranges from 478 g -  752 g, thick pellicle ranges from 0.61 cm - 1.13 cm, the fiber content ranges from 3.63 % - 4.44 % and textures ranges from 3.62 mm/g.second - 3.93 mm/g.second with panelists preference level generally not significantly different for all parameters (except the 4 % sucrose treatment) with the grading scale rather like until like.  Keywords : Nata, sucrose, dragon fruit peel